2018
DOI: 10.1111/ijd.14107
|View full text |Cite
|
Sign up to set email alerts
|

Effective permeation of 2.5 and 5% lidocaine hydrochloride in human skin using iontophoresis technique

Abstract: Study shows that modulated IOP can be a promising alternative method in clinical settings aside from continuous IOP. Based on the clinical requirements, IOP can be used at 2.5 and 5% lidocaine concentration depending on need of relatively short or very short onset action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Topical anesthetics like LID block reversibly the free nerve-ending conductions in the dermis and mucosa. This process can be limited by drug diffusion through the epidermis, since in healthy skin the drug has to pass through the stratum corneum to reach dermal tissue at therapeutic concentrations [ 56 ]. The versatility of 3D-bioprinting was exploited in this work to produce different types of skin substitutes (full-thickness healthy skin and dermal layer tissue) to study the effect of epidermis barrier on LID diffusion and to mimic the open wound skin tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Topical anesthetics like LID block reversibly the free nerve-ending conductions in the dermis and mucosa. This process can be limited by drug diffusion through the epidermis, since in healthy skin the drug has to pass through the stratum corneum to reach dermal tissue at therapeutic concentrations [ 56 ]. The versatility of 3D-bioprinting was exploited in this work to produce different types of skin substitutes (full-thickness healthy skin and dermal layer tissue) to study the effect of epidermis barrier on LID diffusion and to mimic the open wound skin tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results showed that H90 1 P 2 -L had the highest amount of released lidocaine HCl, which was a significant difference from H5 1 P 2 -L and H50 1 P 2 -L. At 60 min, the results had related to dissolving ability, since H90 1 P 2 -L showed the fastest dissolving ability. Thus, H90 1 P 2 -L should release the highest amount of lidocaine HCl, while the needles of H5 1 P 2 -L and H50 1 P 2 -L did not completely dissolve, so the released amount of lidocaine HCl was lower than for H90 1 P 2 -L. Interestingly, all three formulations provided an adequate released amount of lidocaine HCl to reach an anesthetic effect (approximately 135 μg/cm 2 or 239 μg/1.77 cm 2 ) [ 20 ]. Moreover, the released amount of lidocaine HCl will not cause the side effects since the toxic dose of lidocaine HCl is when the dose exceeds 4.5 mg/kg [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lidocaine HCl is generally administered via an intravenous or intramuscular injection to provide a high bioavailability, but it causes pain during insertion [ 18 ]. Due to its poor permeability, the slow penetration of lidocaine HCl is a major drawback of its topical use, since it typically takes at least ~1–2 h to reach a therapeutic effect [ 20 ]. However, lidocaine HCl shows a rapid onset of action (~20–60 s) [ 21 ], which is promising for its use with dissolving MNs, which can rapidly provide the therapeutic anesthetic effect of lidocaine HCl through the skin without pain during skin insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Ibuprofen is a very popular non-steroidal analgesic and anti-inflammatory drug [ 20 ]. The lidocaine is used as topical anesthetic in dermatology and cosmetology to alleviate the pain from non-surgical cosmetic procedures [ 60 ]. Caffeine is very popular anti-aging agent applied in cosmetic preparations.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vitro penetration experiments, an abdomen porcine skin was used due to their similar permeability to human skin. Numerous histopathological studies confirmed its similarity to human skin [60,61]. The porcine skin obtained from the local slaughterhouse was used.…”
Section: In Vitro Skin Permeation Studiesmentioning
confidence: 99%